Foamed cement-based sound absorption material with adjustable and controllable pore structure and preparation method of foamed cement-based sound absorption material
By combining physical-chemical collaborative foaming method and vacuum freeze-drying method, using micropore structure adjusting agent and composite foaming agent, a three-stage temperature-controlled freeze-drying process is designed, which solves the problems of insufficient control of pore structure and limited sound absorption performance of cement-based porous sound-absorbing materials, and achieves efficient and low-cost noise control effect.
Patent Information
- Application Number
- CN202510287479.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-12
AI Technical Summary
The existing cement-based porous sound-absorbing materials have problems such as insufficient pore structure regulation, limited sound absorption performance, and high cost, making it difficult to effectively reduce noise pollution in the built environment.
The physical-chemical collaborative foaming method is combined with vacuum freeze-drying method, and the micropore structure adjuster, composite foaming agent and composite pore-forming agent are added to design a three-stage temperature-controlled freeze-drying process to achieve accurate regulation of pore structure and improve sound absorption performance.
It significantly improves the complexity of the pore structure and opening porosity of the material, improves sound absorption performance, solves problems such as insufficient pore structure regulation, limited sound absorption performance, and high cost, providing an efficient and low-cost solution for noise pollution control in the built environment.
Smart Images

Figure CN119774957A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building functional materials, and in particular to a foam cement-based sound-absorbing material with adjustable pore structure and a preparation method thereof. Background Art
[0002] With the rapid development of urbanization, industrialization and transportation, noise pollution has become one of the major environmental problems facing human society. According to a report by the World Health Organization, long-term exposure to noise pollution will seriously affect human physical and mental health, and the vibration caused by noise will also accelerate the aging of mechanical equipment and building structures. Therefore, it is urgent to take effective measures to alleviate the harm caused by noise pollution. In view of the propagation characteristics of noise, the use of sound-absorbing materials to control the propagation path is the simplest and most efficient.
[0003] According to the noise mechanism, sound-absorbing materials are divided into resonant and porous sound-absorbing materials. Among them, the application of resonant sound-absorbing materials is severely limited due to their narrow sound absorption band, while porous sound-absorbing materials have been widely used in passive noise control due to their advantages in effective absorption of high frequencies and broadbands, convenient material selection, light weight, and relatively lower costs.
[0004] At present, commonly used porous sound-absorbing materials include mineral materials, synthetic materials, and metal materials. However, due to their poor durability and adaptability, high cost and other issues, the long-term application of the above raw materials in building structures still faces challenges. On the contrary, cement-based materials, as typical structural materials, provide excellent choices in terms of cost-effectiveness, durability and mechanical properties, making them the most commonly used building materials. Therefore, the development of architectural porous sound-absorbing materials with good sound absorption properties is of great significance to reduce noise pollution in the building environment.
[0005] The invention patent (publication number CN115010513A) uses tailings, construction waste, gypsum, fly ash, cement, etc. as the main raw materials, uses hydrogen peroxide to decompose on the surface and inside of the sound-absorbing board to obtain a large number of circular holes, and then uses a foaming agent with a slightly higher decomposition temperature to decompose during the autoclave curing process to achieve pore formation, and prepares a cement-based porous sound-absorbing material. In the embodiment, the open porosity is greater than 64~70%. The use of autoclave curing in this technology leads to high energy consumption costs, while this technology innovatively uses a physical-chemical synergistic foaming method combined with a freeze-drying method and adds a microporous structure adjuster, and the open porosity can reach a higher 70~85%, the pore structure is richer, more complex, and the energy consumption is lower.
[0006] The invention patent (publication number CN110255987A) uses the anionic surfactant α-olefin sulfonate to foam on the basis of ordinary cement, leaving more pores during natural air drying to obtain a foam cement-based porous sound-absorbing material. This technology only uses α-olefin sulfonate anionic surfactant as a physical foaming agent. The pore size of the obtained foam cement-based sound-absorbing material is 3mm~15mm and the porosity is 15~30%. This technology can adjust the dosage and ratio of the microporous structure adjuster, composite foaming agent, and composite pore-forming agent to obtain a sound-absorbing material with a density of 200~1000kg / m 3 The foam cement-based sound-absorbing material with a porosity of 60~90%, a pore size coverage range of 2nm~6mm, and an open porosity of 70~85% can achieve precise control of the pore structure. The material not only has a greater internal tortuosity, but also has a larger internal porosity, which greatly improves the sound absorption performance of the material.
[0007] The invention patent (publication number CN115353365A) adopts alkali excitation technology, uses waste incineration ash, granulated blast furnace slag and fly ash as precursors, and supplemented with a foaming agent (aluminum powder) to prepare a porous cement sound-absorbing material. The noise reduction coefficient in the embodiment is 0.05~0.25, and the noise reduction ability is poor. The noise reduction coefficient of the foamed cement-based sound-absorbing material prepared by this technology is 0.12~0.64, which has better sound absorption performance.
[0008] The invention patent (publication number CN103739306A) discloses a method for preparing directional porous cement, using tert-butyl alcohol, alkene, alkene ketone, alkene-naphthalene blend as organic pore-forming agents, and the porous material prepared by the four steps of cement-based slurry preparation, frozen green body preparation, freeze-drying method to prepare cement-based porous green body, and green body curing has an open porosity of about 50~80%. The invention patent (publication number CN106892674A) discloses a method for preparing gradient directional porous cement based on the freezing molding technology of a two-phase pore-forming agent system, by stirring and mixing cement powder with a mixed solution based on a two-phase pore-forming agent system (water and tert-butyl alcohol) into a uniform system, and then freezing molding, freeze drying, and curing to obtain a gradient directional porous cement material. In the embodiment, the open porosity is 40.21~62.81%. The invention patent (publication number CN107619226A) discloses a porous cement membrane and its preparation method and use. Water is used as a pore-forming agent, and a porous cement membrane with a directional pore structure is prepared through a freeze-molding process, and its porosity is 40~70%. The difference of this technology is that a mixed solution of ethylene glycol, benzyl alcohol and cyclohexanol is used as a composite pore-forming agent. Based on the different freezing points and sublimation characteristics of the three, a three-stage temperature-controlled freeze-drying process is innovatively designed, which can achieve full crystallization and segmented sublimation removal of water and composite pore-forming agents, and innovatively combines physical-chemical foaming methods and microporous structure regulators to achieve effective design of pore structure and sound absorption performance. The porosity is 60~90%, and the open porosity can reach a higher 70~85%. The freeze-sublimation process is more reasonable, ensuring the strength of the material.
[0009] In summary, although the cement-based porous sound-absorbing materials in the prior art have made certain progress in sound absorption performance, there are still problems such as insufficient pore structure regulation, limited sound absorption performance, and high cost. The present invention uses cement slurry as the main component, innovatively combines the physical-chemical synergistic foaming method with the vacuum freeze-drying method, and adjusts the dosage and component ratio of the micropore structure regulator, the composite foaming agent, and the composite pore-forming agent to achieve precise control of the pore structure. At the same time, a three-stage temperature-controlled freeze-drying process is designed, which significantly improves the complexity of the material's pore structure and the open porosity, thereby effectively improving the sound absorption performance of the material, solving the problems of insufficient pore structure regulation, limited sound absorption performance, and high cost in the prior art, and providing an efficient and low-cost solution for noise pollution control in the building environment. Summary of the invention
[0010] In view of the problems of high density, difficult to control pore structure, poor sound absorption performance and high cost of traditional building sound absorbing materials, an object of the present invention is to provide a foam cement-based sound absorbing material with adjustable pore structure. The sound absorbing material has the advantages of low bulk density, adjustable density, pore coverage, proportion of pores of different levels, porosity and open porosity, light weight and high strength, good sound absorption performance, low cost, fireproof and non-combustible, good durability, etc., thereby achieving effective control of noise in the building environment.
[0011] The above-mentioned object of the present invention is achieved by the following technical solutions: A foam cement-based sound-absorbing material with adjustable pore structure, the raw materials of which include, by weight: 1000-1300 parts of P.O42.5R silicate cement, 400-600 parts of water, 20-100 parts of composite foaming agent, 10-35 parts of micropore structure adjusting agent, 5-30 parts of composite pore-forming agent, and 1-20 parts of accelerating agent. The density of the foam cement-based sound-absorbing material is 200-1000 kg / m 3 , thickness is 20~60mm, porosity is 60~90%, pore size coverage range is 2nm~6mm, and open porosity is 70~85%.
[0012] In the present technical solution, by adjusting the dosage and component ratio of the composite foaming agent, the material density, total porosity, and the proportion of pores at the μm and mm levels can be controlled. Secondly, for foam cement-based sound-absorbing materials, porosity is the key to sound energy loss. When the density of the material is too small and its porosity is too large, it will cause impedance mismatch between the material and the air, and the sound waves lost inside the foam cement-based sound-absorbing material will be greatly reduced. At the same time, the mechanical properties of the material will be significantly reduced. When the density is too large, its porosity is too low, which makes it difficult for sound waves to enter the material. Preferably, the density of the foam cement-based sound-absorbing material is 200~1000kg / m 3 , the porosity is 60~90%.
[0013] In one or more embodiments, the composite foaming agent includes 30 wt.% hydrogen peroxide solution, potassium lauryl phosphate, calcium stearate and coconut oil diethanolamide.
[0014] Furthermore, the mass ratio of 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate and coconut oil diethanolamide is (22-28): (8-14): (1-6): (1-3). In the technical scheme, a composite foaming agent with a mass ratio of 30wt.% hydrogen peroxide, potassium dodecyl phosphate, calcium stearate and coconut oil diethanolamide of (22-28): (8-14): (1-6): (1-3) is used. When forming pores by a physical-chemical synergistic foaming method, on the one hand, a large number of closed pores are formed inside the matrix by the physical foaming agent (dodecyl phosphate), and on the other hand, the adjacent pores are connected by the continuous air entrainment effect of the decomposition of the chemical foaming agent (hydrogen peroxide), thereby forming a large number of connected pores inside the material. In addition, potassium dodecyl phosphate foaming mainly contributes to μm-level pores, while hydrogen peroxide foaming mainly contributes to mm-level pores, thus forming a complementary effect, making the pore distribution more reasonable, and the proportion of μm-level and mm-level pores of the material can be regulated by adjusting the ratio of hydrogen peroxide to potassium dodecyl phosphate. The addition of calcium stearate and coconut oil diethanolamide foam stabilizing ingredients is conducive to the retention of bubbles in the slurry, making it less likely to break or prolonging the rupture time. The yield rate of foam cement-based sound-absorbing materials is higher and it is easier to reach the set density.
[0015] In the present technical solution, for foam cement-based sound-absorbing materials, different thicknesses will show different sound absorption characteristics. Generally speaking, materials with moderate thickness have better sound absorption performance in the medium and high frequency bands, while thicker materials perform better in the low frequency bands. However, when the thickness of the material is too large, its low-frequency sound absorption performance may decrease, because too thick materials may cause sound waves to reflect and interfere inside the material, thereby affecting the sound absorption effect. At the same time, too thick materials may cause problems such as excessive space occupation and construction difficulties. Therefore, preferably, the thickness of the foam cement-based sound-absorbing material prepared by the present technical solution is 20~60mm.
[0016] In this technical solution, by adjusting the dosage and component ratio of the micropore structure regulator, the proportion of nm-level micropores in the foam cement-based sound-absorbing material can be controlled, and a larger porosity and a more complex pore structure can be obtained with higher strength, thereby improving the sound absorption performance of the material.
[0017] In one or more embodiments, the micropore structure regulator includes sepiolite powder, zeolite powder and diatomaceous earth.
[0018] Furthermore, the mass ratio of the sepiolite powder, zeolite powder and diatomaceous earth is (7-12): (1-5): (2-3). In the present technical scheme, a microporous structure regulator is used in which the mass ratio of sepiolite powder, zeolite powder and diatomaceous earth is (7-12): (1-5): (2-3). Among them, sepiolite powder has a special interlayer structure, zeolite powder has a unique spatial network structure, and diatomaceous earth has a fine and porous microstructure. Although the three have different internal structures, they are all rich in nm-level micropores, have a large specific surface area, and have good water absorption. In addition, they also have certain volcanic ash activity. When an appropriate amount of microporous structure regulator is added to the foam cement-based sound-absorbing material, the water absorbed by the microporous structure regulator can be sublimated to form pores during the freeze-drying process. The volcanic ash activity of the microporous structure regulator can also be used to react with cement to increase the strength and durability of the material. Furthermore, with the synergistic effect of sepiolite powder, zeolite powder and diatomaceous earth, it can ensure that the foam cement-based sound-absorbing material has sufficient mechanical properties and can regulate the pore proportion at the nm level, further increasing the porosity and pore complexity of the material.
[0019] In addition, if the porosity, pore morphology and thickness of two foam cement-based sound-absorbing material samples are the same, then the sample with a smaller pore size will have more pores inside and the overall pore network structure will be more complex. The number of reflections and refractions generated by sound waves passing through the pores will increase greatly, the contact area between the air inside the material and its adjacent pore walls will increase, and the energy loss caused by friction and heat transfer generated by relative movement will also increase. The sound energy absorbed by the material sample will increase, thereby improving the sound absorption performance. If the relative pore size is too small, it will be difficult for the sound wave to enter the interior of the material, and direct reflection will occur on its surface, and the sound absorption performance will be greatly reduced. Therefore, the pore size of the foam cement-based sound-absorbing material should not be too large or too small, and there will be an optimal pore size range that makes its sound absorption performance the best. Preferably, the pore size coverage range of the foam cement-based sound-absorbing material prepared by the present technical solution is 2nm~6mm.
[0020] In the present technical solution, by adjusting the dosage and component ratio of the composite pore-forming agent, foam cement-based sound-absorbing materials with different open porosities under the same density and pore size coverage range can be obtained. Generally speaking, the sound absorption performance of materials with high open porosity is better than that of materials with low open porosity, but this is not entirely certain. The size of the open porosity not only determines the complexity of the internal pore structure, but also directly affects the flow resistivity of the material, thereby changing the sound absorption performance of the material. Preferably, the open porosity of the foam cement-based sound-absorbing material prepared by the present technical solution is preferably 70~85%.
[0021] In one or more embodiments, the composite pore former includes ethylene glycol, benzyl alcohol and cyclohexanol.
[0022] Furthermore, the mass ratio of ethylene glycol, benzyl alcohol and cyclohexanol is (6-8): (1-2): (1-2). In the present technical solution, the composite pore former with a mass ratio of ethylene glycol, benzyl alcohol and cyclohexanol of (6-8): (1-2): (1-2) is beneficial to maximize the open porosity and optimize the connectivity of the material. Ethylene glycol, benzyl alcohol and cyclohexanol are all non-polar or weakly polar organic substances, which have no reaction with cement, ensuring that the pore structure is stably formed during the curing process. The three have different freezing points and sublimation characteristics, forming crystals of different shapes during freezing, and will undergo cross-linking during the growth process to form internally connected pores and channels. This structure will be retained after sublimation, so that the foam cement-based sound-absorbing material has better pore connectivity and structural stability.
[0023] In this technical solution, the stability of the foam is very important during the foaming process. Therefore, adding a shotcrete liquid accelerating agent to the cement-based foam slurry significantly accelerates the coagulation and hardening process of the foam slurry, stabilizes and fixes the bubbles in a short time, and prevents the bubbles from bursting before being fixed and causing mold collapse. At the same time, adding a foam-stabilizing component to the composite foaming agent allows the bubbles generated by the physical-chemical synergistic foaming method to be stably stored in the slurry to avoid overflow or combined bubbles.
[0024] Another object of the present invention is to provide a method for preparing a foam cement-based sound-absorbing material with adjustable pore structure, the method specifically comprising the following steps: S1. P.O42.5R silicate cement, water, accelerator, micropore structure regulator and composite pore former are weighed according to the mass ratio, and stirred in a high-speed stirrer at a speed of 1500-3000 rad / min for 2-4 min to obtain a composite cement slurry; S2. After adding the composite foaming agent to the composite cement slurry obtained in S1, stirring at a speed of 1500~3000rad / min for 30~45s, and then continuing to stir at a speed of 6000~8000rad / min for 15~25s to obtain a composite cement-based foam slurry; S3. The composite cement-based foam slurry obtained in S2 is quickly poured into a mold, and allowed to stand for foaming for 20 to 48 hours at room temperature (20 to 30° C.) and a relative humidity of 50 to 90% to obtain a composite foam cement-based material; S4. placing the fully foamed and solidified composite foam cement-based material in S3 in a -5°C freezer for 20 to 36 hours, so that the water and the composite pore-forming agent in the composite foam cement-based material are fully crystallized at low temperature to obtain a frozen foam cement-based material; S5. freeze-dry the frozen foam cement-based material obtained in S4 using a vacuum freeze dryer, with a vacuum degree of 0.1-5 Pa and freezing for 20-48 hours to further complete the pore structure regulation; S6. Finally, the material obtained in S5 is transferred into a standard curing box, and after curing for a specified time, a foam cement-based sound-absorbing material is obtained.
[0025] In one or more embodiments, the composite cement-based foam slurry is poured into a mold with a diameter of 100 mm and a height of 50 mm, and allowed to stand for 20 to 48 hours to fully foam. At the same time, the composite cement-based foam slurry is hydrated at an early stage to form a certain amount of gelling material, so that the cement particles are bonded together, which is convenient for the subsequent preparation process.
[0026] In some embodiments, the fully foamed and solidified composite foam cement matrix material in S3 is placed in a -5°C freezer for 20 to 36 hours. The purpose is to allow the water and the composite pore-forming agent in the composite foam cement matrix material to crystallize at low temperature. Secondly, the pre-freezing at -5°C is to avoid cracking of the cement matrix due to excessively low temperature.
[0027] In some embodiments, the frozen foam cement-based material obtained in S4 is placed in a vacuum freeze dryer for vacuum freeze drying treatment, the vacuum degree is 0.1~5Pa, and the freeze drying process is divided into three stages, the first stage is -15~0℃, and the freeze drying time is 10~16h; the second stage is -30~-15℃, and the freeze drying time is 6~12h; the third stage is -45~-30℃, and the freeze drying time is 4~8h, so that water and the composite pore-forming agent are fully crystallized and sublimated to form pores in different temperature zones, while avoiding cracking of the cement matrix. In the first stage of vacuum freeze drying (-15~0℃), the water in the foam cement-based sound-absorbing material is completely sublimated, and the benzyl alcohol is partially sublimated to perform preliminary pore opening; in the second stage of vacuum freeze drying (-30~-15℃), the remaining benzyl alcohol and ethylene glycol are sublimated to form a stepped pore formation; in the third stage of vacuum freeze drying (-45~-30℃), cyclohexanol is rapidly sublimated to reduce the blockage of the pore wall by the residue, and finally the water and the composite pore-forming agent in the material are completely left in the form of gas, so that the hydration in the standard curing box in the later stage is not affected by it, thereby ensuring the standardization and consistency of the curing conditions and reducing the error of the mechanical properties of the specimens.
[0028] In this technical scheme, according to the experimental materials and experimental preparation method of the present invention, foam cement-based sound absorbing materials with different pore complexities can be obtained: foam cement-based sound absorbing materials with different density levels, foam cement-based sound absorbing materials with different pore coverage ranges and pore proportions at the same density level, and foam cement-based sound absorbing materials with different open porosities at the same density level, ultimately achieving effective design of the pore structure and sound absorption performance of the foam cement-based sound absorbing material.
[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention innovatively adopts a physical-chemical synergistic foaming method combined with a vacuum freeze-drying method, introduces a multi-component synergistic effect of a micropore structure adjuster, a composite foaming agent and a composite pore-forming agent, and realizes multi-dimensional regulation of different pore proportions (nm, μm and mm), different pore diameter coverage ranges, different porosities and different open porosities of the foam cement-based sound-absorbing material, thereby obtaining a foam cement-based sound-absorbing material with low density, high open porosity and high strength, thereby effectively dissipating sound energy. By adjusting the pore structure, it not only effectively reduces the harm of noise pollution, but also gives full play to the structural characteristics, durability and low cost characteristics of inorganic mineral building materials; 2. The present invention designs a microporous structure regulator, adjusts the dosage and component ratio of the microporous structure regulator in the foam cement-based sound-absorbing material, utilizes the volcanic ash activity of the microporous structure regulator to react with cement to increase the strength of the material, and cooperates with the vacuum freeze-drying method to sublimate and remove ice crystals in its own nano-level pores, so that the foam cement-based sound-absorbing material can regulate the proportion of nano-level pores while having sufficient mechanical properties, and further increase the porosity and pore complexity; 3. The present invention designs a three-stage temperature-controlled freeze-drying process. Specifically, according to the different freezing points and sublimation characteristics of water and the composite pore-forming agent, a three-stage temperature-controlled (from -15~0℃ to -30~-15℃ and then to -45~-30℃) vacuum freeze-drying process is designed, and the vacuum freeze-drying time in different stages is regulated according to the dosage and component ratio of the composite pore-forming agent to achieve sufficient crystallization and sublimation of water and the composite pore-forming agent, avoid the destruction of the pore structure caused by the coarsening of ice crystals, achieve a high open porosity, thereby increasing the sound absorption capacity of the foam cement-based sound-absorbing material. At the same time, the setting of various experimental condition parameters in the preparation process of the foam cement-based sound-absorbing material is explored to provide a reference for the preparation of new building functional materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation on the embodiments of the present invention. In the accompanying drawings: Figure 1 This is a method step diagram of a foam cement-based sound-absorbing material with adjustable pore structure and a preparation method thereof provided by the present invention; Figure 2 This is a physical picture of a foam cement-based sound-absorbing material with adjustable pore structure provided by the present application; Figure 3 This is a physical comparison diagram of the surface pore structure of embodiments of different pore diameter coverage ranges at the same density level provided by the present invention. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0032] All raw materials of the present invention are not particularly limited in their sources and can be purchased on the market or prepared according to conventional methods known to those skilled in the art; There is no particular limitation on the purity of all raw materials in the present invention, but analytically pure materials are preferred. All raw materials of the present invention, their brands and abbreviations are conventional brands and abbreviations in the field, and each brand and abbreviation is clear and definite in the field of its related use. Those skilled in the art can purchase them from the market or prepare them by conventional methods according to the brands, abbreviations and corresponding uses.
[0033] Example 1: In parts by weight, the raw materials include: 1100 parts of P.O42.5R Portland cement, 550 parts of water, 80 parts of composite foaming agent, 16 parts of microporous structure regulator, and 8 parts of accelerating agent; The main raw materials of the composite foaming agent are 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide, and the mass ratio of the 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide is 28:14:6:2; The main raw materials of the microporous structure adjusting agent are sepiolite powder, zeolite powder and diatomaceous earth, and the mass ratio of the sepiolite powder, zeolite powder and diatomaceous earth is 7:2:2; Among them, the quick-setting agent is a liquid quick-setting agent for shotcrete.
[0034] The specific steps are as follows: (1) P.O42.5R silicate cement, water, accelerator, micropore structure regulator and composite pore former were weighed according to the mass ratio, and stirred in a high-speed stirrer at a speed of 2000 rad / min for 3 min to obtain a composite cement slurry; (2) adding a composite foaming agent to the composite cement paste obtained in S1, stirring at a speed of 1600 rad / min for 35 seconds, and then stirring at a speed of 7600 rad / min for 20 seconds to obtain a composite cement-based foam paste; (3) The composite cement-based foam slurry obtained in (2) is quickly poured into a mold, and allowed to stand for foaming for 24 hours in an environment with a room temperature of 25° C. and a humidity of 90%, thereby obtaining a composite foam cement-based material; (4) The composite foam cement-based material obtained in (3) is transferred into a standard curing box and cured for a specified time to obtain a foam cement-based sound-absorbing material.
[0035] Example 2: In parts by weight, the raw materials include: 1100 parts of P.O42.5R silicate cement, 550 parts of water, 80 parts of composite foaming agent, 22 parts of microporous structure regulator, and 8 parts of accelerating agent; The main raw materials of the composite foaming agent are 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide, and the mass ratio of the 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide is 26:11:4:1; The remaining steps are the same as those in Example 1.
[0036] Example 3: In parts by weight, the raw materials include: 1100 parts of P.O42.5R silicate cement, 550 parts of water, 80 parts of composite foaming agent, 25 parts of microporous structure regulator, and 8 parts of accelerating agent; The main raw materials of the composite foaming agent are 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide, and the mass ratio of the 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide is 25:10:3:1; The remaining steps are the same as those in Example 1.
[0037] Example 4: In parts by weight, the raw materials include: 1100 parts of P.O42.5R Portland cement, 550 parts of water, 80 parts of composite foaming agent, 30 parts of microporous structure regulator, and 8 parts of accelerating agent; The main raw materials of the composite foaming agent are 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide, and the mass ratio of the 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide is 24:9:2:1; The remaining steps are the same as those in Example 1.
[0038] Example 5: In parts by weight, the raw materials include: 1100 parts of P.O42.5R Portland cement, 550 parts of water, 80 parts of composite foaming agent, 32 parts of microporous structure regulator, and 8 parts of accelerating agent; The main raw materials of the composite foaming agent are 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide, and the mass ratio of the 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide is 22:8:1:1; The remaining steps are the same as those in Example 1.
[0039] Example 6: In parts by weight, the raw materials include: 1100 parts of P.O42.5R silicate cement, 550 parts of water, 80 parts of composite foaming agent, 22 parts of micropore structure regulator, 10 parts of composite pore former, and 8 parts of accelerating agent; The main raw materials of the composite foaming agent are 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide, and the mass ratio of the 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate, and coconut oil diethanolamide is 26:11:4:1; The main raw materials of the microporous structure adjusting agent are sepiolite powder, zeolite powder and diatomaceous earth, and the mass ratio of the sepiolite powder, zeolite powder and diatomaceous earth is 7:2:2; The main raw materials of the composite pore-forming agent are ethylene glycol, benzyl alcohol and cyclohexanol, and the mass ratio of ethylene glycol, benzyl alcohol and cyclohexanol is 8:2:1; Among them, the quick-setting agent is a liquid quick-setting agent for shotcrete.
[0040] The specific steps are as follows: (1) P.O42.5R silicate cement, water, accelerator, micropore structure regulator and composite pore former were weighed according to the mass ratio, and stirred in a high-speed stirrer at a speed of 2000 rad / min for 3 min to obtain a composite cement slurry; (2) adding a composite foaming agent to the composite cement paste obtained in (1), stirring at a speed of 1600 rad / min for 35 seconds, and then stirring at a speed of 7600 rad / min for 20 seconds to obtain a composite cement-based foam paste; (3) The composite cement-based foam slurry obtained in (2) is quickly poured into a mold, and allowed to stand for foaming for 24 hours in an environment with a room temperature of 25° C. and a humidity of 90%, thereby obtaining a composite foam cement-based material; (4) placing the composite foam cement-based material that has been fully foamed and solidified in (3) in a -5°C freezer for 20 hours, so that the water and the composite pore-forming agent in the composite foam cement-based material are fully crystallized at low temperature, thereby obtaining a frozen foam cement-based material; (5) freeze-drying the frozen foam cement-based material obtained in (4) using a vacuum freeze dryer with a vacuum degree of 0.1 Pa. The freeze-drying process is divided into three stages: the first stage is -15~0°C, the freeze-drying time is 10 h, the second stage is -30~-15°C, the freeze-drying time is 6 h, and the third stage is -45~-30°C, the freeze-drying time is 4 h, so that the water in the frozen foam cement-based material and the composite pore-forming agent are fully crystallized and sublimated, and the pore structure regulation is further completed; (6) Finally, the material obtained in (5) is transferred into a standard curing box and cured for a specified time to obtain a foam cement-based sound absorbing material.
[0041] Example 7: In parts by weight, the raw materials include: 1100 parts of P.O42.5R silicate cement, 550 parts of water, 80 parts of composite foaming agent, 22 parts of micropore structure regulator, 14 parts of composite pore former, and 8 parts of accelerating agent; In step (5), the frozen foam cement-based material obtained in (4) is freeze-dried at a vacuum degree of 0.1 Pa. The freeze-drying process is divided into three stages: the first stage is -15~0°C, the freeze-drying time is 11 hours, the second stage is -30~-15°C, the freeze-drying time is 7 hours, and the third stage is -45~-30°C, the freeze-drying time is 5 hours, so that the water in the frozen foam cement-based material and the composite pore-forming agent are fully crystallized and sublimated, and the pore structure regulation is further completed; The remaining steps are the same as those in Example 6.
[0042] Example 8: In parts by weight, the raw materials include: 1100 parts of P.O42.5R silicate cement, 550 parts of water, 80 parts of composite foaming agent, 22 parts of micropore structure regulator, 18 parts of composite pore forming agent, and 8 parts of accelerating agent; In step (5), the frozen foam cement-based material obtained in (4) is freeze-dried at a vacuum degree of 0.1 Pa. The freeze-drying process is divided into three stages: the first stage is -15~0°C, the freeze-drying time is 11 hours, the second stage is -30~-15°C, the freeze-drying time is 8 hours, and the third stage is -45~-30°C, the freeze-drying time is 6 hours, so that the water in the frozen foam cement-based material and the composite pore-forming agent are fully crystallized and sublimated, and the pore structure regulation is further completed; The remaining steps are the same as those in Example 6.
[0043] Example 9: In parts by weight, the raw materials include: 1100 parts of P.O42.5R silicate cement, 550 parts of water, 80 parts of composite foaming agent, 22 parts of micropore structure adjusting agent, 22 parts of composite pore forming agent, and 8 parts of accelerating agent; In step (5), the frozen foam cement-based material obtained in (4) is freeze-dried at a vacuum degree of 0.1 Pa. The freeze-drying process is divided into three stages: the first stage is -15~0°C, the freeze-drying time is 13 hours, the second stage is -30~-15°C, the freeze-drying time is 11 hours, and the third stage is -45~-30°C, the freeze-drying time is 6 hours, so that the water in the frozen foam cement-based material and the composite pore-forming agent are fully crystallized and sublimated, and the pore structure regulation is further completed; The remaining steps are the same as those in Example 6.
[0044] Example 10: In parts by weight, the raw materials include: 1100 parts of P.O42.5R silicate cement, 550 parts of water, 80 parts of composite foaming agent, 22 parts of micropore structure adjusting agent, 26 parts of composite pore forming agent, and 8 parts of accelerating agent; In step (5), the frozen foam cement-based material obtained in (4) is freeze-dried at a vacuum degree of 0.1 Pa. The freeze-drying process is divided into three stages: the first stage is -15~0°C, the freeze-drying time is 15 hours, the second stage is -30~-15°C, the freeze-drying time is 12 hours, and the third stage is -45~-30°C, the freeze-drying time is 7 hours, so that the water in the frozen foam cement-based material and the composite pore-forming agent are fully crystallized and sublimated, and the pore structure regulation is further completed; The remaining steps are the same as those in Example 6.
[0045] Example 11: After the foamed cement-based sound absorbing materials P1~P10 were prepared by Examples 1 to 10, the sound absorption performance and mechanical properties of the foamed cement-based sound absorbing materials were tested by an impedance tube and a universal testing machine, respectively. The average sound absorption coefficient, noise reduction coefficient and compressive strength of the foamed cement-based sound absorbing materials with different pore structures are shown in Table 1.
[0046] Table 1: As shown in Table 1, by adding appropriate amounts of composite foaming agent, microporous structure adjusting agent, composite pore forming agent, accelerating setting agent and other components to cement, a foam cement-based sound-absorbing material with adjustable pore structure can be obtained. By adjusting the pore structure, the ability of the material to attenuate sound waves can be greatly improved, which not only effectively reduces the harm of noise pollution, but also gives full play to the structural characteristics, durability and low cost of inorganic mineral building materials. When the density of the foam cement-based sound-absorbing material is 400kg / m 3 When the total porosity is 82.8% and the open porosity is 73.1%, the 28d compressive strength is 2.98MPa, the average sound absorption coefficient reaches 0.62, and the noise reduction coefficient reaches 0.64. The adjustability of the pore structure is achieved, and the sound absorption performance of the foam cement-based sound-absorbing material is improved in a targeted and effective manner.
[0047] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A foam cement-based sound-absorbing material with adjustable pore structure, characterized in that: The raw materials include, by weight: 1000-1300 parts of P.O42.5R silicate cement, 400-600 parts of water, 20-100 parts of composite foaming agent, 10-35 parts of micropore structure adjusting agent, 5-30 parts of composite pore-forming agent, and 1-20 parts of accelerating setting agent.
2. The foam cement-based sound-absorbing material with adjustable pore structure according to claim 1, characterized in that: The main raw materials of the composite foaming agent are 30wt.% hydrogen peroxide solution, potassium dodecyl phosphate, calcium stearate and coconut oil diethanolamide, which are weighed respectively in a mass ratio of (22-28): (8-14): (1-6): (1-3) and stirred to mix evenly to obtain a composite foaming agent.
3. The foam cement-based sound-absorbing material with adjustable pore structure according to claim 1, characterized in that: The main raw materials of the microporous structure regulator are sepiolite powder, zeolite powder and diatomaceous earth, which are weighed respectively in a mass ratio of (7-12): (1-5): (2-3), stirred and mixed evenly, and immersed in excess water until saturated, and then filtered to obtain the microporous structure regulator.
4. The foam cement-based sound-absorbing material with adjustable pore structure according to claim 1, characterized in that: The composite pore-forming agent is mainly composed of raw materials ethylene glycol, benzyl alcohol and cyclohexanol mixed in proportion, and the mass ratio is (6~8): (1~2): (1~2).
5. The method for preparing a foam cement-based sound-absorbing material with adjustable pore structure according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. P.O42.5R silicate cement, water, accelerator, micropore structure regulator and composite pore former are weighed according to the mass ratio, and stirred in a high-speed stirrer at a speed of 1500-3000 rad / min for 2-4 min to obtain a composite cement slurry; S2. After adding the composite foaming agent to the composite cement slurry obtained in S1, stirring at a speed of 1500~3000rad / min for 30~45s, and then continuing to stir at a speed of 6000~8000rad / min for 15~25s to obtain a composite cement-based foam slurry; S3. The composite cement-based foam slurry obtained in S2 is quickly poured into a mold, and allowed to stand for foaming for 20 to 48 hours at room temperature (20 to 30° C.) and a relative humidity of 50 to 90% to obtain a composite foam cement-based material; S4. placing the fully foamed and solidified composite foam cement-based material in S3 in a -5°C freezer for 20 to 36 hours, so that the water and the composite pore-forming agent in the composite foam cement-based material are fully crystallized at low temperature to obtain a frozen foam cement-based material; S5. freeze-dry the frozen foam cement-based material obtained in S4 using a vacuum freeze dryer, with a vacuum degree of 0.1-5 Pa and freezing for 20-48 hours to further complete the pore structure regulation; S6. Finally, the material obtained in S5 is transferred into a standard curing box, and after curing for a specified time, a foam cement-based sound-absorbing material is obtained.
6. The method for preparing a foam cement-based sound-absorbing material with adjustable pore structure according to claim 5, characterized in that: In the step S5, the following steps are specifically included: The frozen foam cement-based material obtained in S4 is placed in a vacuum freeze dryer for vacuum freeze drying. The freeze drying process is divided into three stages. The first stage is -15~0℃, and the freeze drying time is 10~16h; the second stage is -30~-15℃, and the freeze drying time is 6~12h; the third stage is -45~-30℃, and the freeze drying time is 4~8h. Finally, water and the composite pore-forming agent are fully crystallized and sublimated to form pores in different temperature zones, while avoiding cracking of the cement matrix.
7. The method for preparing a foam cement-based sound-absorbing material with adjustable pore structure according to claim 5, characterized in that: By adjusting the dosage and component ratio of the micropore structure regulator, the proportion of nm-level micropores in the material can be regulated; by adjusting the dosage and component ratio of the composite foaming agent, the material density, total porosity, and the proportion of pores at μm and mm levels can be regulated; and by adjusting the dosage, component ratio and freeze-drying process parameters of the composite pore-forming agent, the material open porosity can be mainly regulated, ultimately achieving effective design of the pore structure and sound absorption performance of the foam cement-based material.
8. The foamed cement-based sound-absorbing material with adjustable pore structure obtained by the method for preparing a foamed cement-based sound-absorbing material with adjustable pore structure according to any one of claims 5 to 7, characterized in that: The density of the foam cement-based sound-absorbing material with adjustable pore structure is 200-1000 kg / m 3 , thickness is 20~60mm, porosity is 60~90%, pore size coverage range is 2nm~6mm, open porosity is 70~85%, 28d compressive strength is 1.83~14.56MPa, the average sound absorption coefficient in the frequency range of 250~2000Hz is 0.12~0.62, and the noise reduction coefficient is 0.14~0.64.
Citation Information
Patent Citations
Preparation method of directional porous special cement
CN103739306A
Method for preparing gradient directional porous cement based on two-phase pore former system freezing molding technology
CN106892674A
Porous cement membrane as well as preparation method and application thereof
CN107619226A
Cement-based foam porous sound absorption material
CN110255987A
Cement-based porous acoustic board and preparation method thereof
CN115010513A
Cited By
Humidity-responsive porous cement-based sound absorption material and preparation method thereof
CN120965236A
Humidity-responsive porous cement-based sound-absorbing material and method for preparing the same
CN120965236B
Preparation method of lightweight efficient sound-absorbing cement-based foam
CN121021070A
Coal gasification slag-based hierarchical pore composite sound absorption material as well as preparation method and application thereof
CN121270172A
A pore-fracture coexisting type hard rock similar material based on recycled internal maintenance material and a preparation method thereof
CN122705229A